Aerosol Concentrations and Fungal Communities Within Broiler Houses in Different Broiler Growth Stages in Summer - Chen, Guozhong; Ma, Di; Huang, Qingrong; Tang, Wenli; Wei, Maolian; Li, Youzhi; Jiang, Linlin; Zhu, Hongwei; Yu, Xin; Zheng, Weibo; Zhang, Jianlong; Zhang, Xingxiao (Frontiers in Veterinary Science, 2021)
Fungal aerosols in broiler houses are important factors that can harm the health of human beings and broiler. To determine the composite characteristics and changes in fungal aerosols in broiler houses during different broiler growth stages in summer. We analyzed the species, concentration and particle diameter distribution characteristics of the aerosols in poultry houses using an Andersen sampler and internal transcribed spacer 1 (ITS1) high-throughput sequencing technology. The concentration of fungal aerosols in the poultry houses increased as the ages of the broiler increased, which was also accompanied by gradual increases in the variety and diversity indices of the fungal communities in the air of the poultry houses. During the entire broiler growth period, the dominant genera in the fungal aerosols in the poultry houses included Trichosporon, Candida, Aspergillus, Cladosporium and Alternaria. These fungi may be harmful to the health of poultry and human beings, so permanent monitoring of microbial air quality in chicken houses is necessary.